Teachers’ autonomy and accountability in assessing students’ physical education in school-based assessment - Md Ali, Ruzlan; Veloo, Arsaythamby (Springer, 2017)
School-Based Assessment (SBA) became the educational policy for Malaysian secondary schools since 2011. SBA recognizes the need for school teachers to be given the autonomy and accountability in assessing their students’ performance. Hence, they are given the freedom to design quality assessment activities aligned with their instructional strategies and students’ learning outcomes. This chapter discusses the case of a physical activity assessment in Physical Education (PE) that focuses on the implementation of the National Test Standard for Students’ Physical Activities. The test comprises the National Physical Fitness Standard (NPFS) and Body-Mass Index (BMI). The NPFS assessment program assesses physical fitness through four activities, namely up-and-down the bench, pumping, star jump, and sit-ups. On the other hand, BMI is determined by dividing the body weight by the height. A total of 30 PE teachers, consisting of 16 non-PE optionists and 14 PE optionists from 15 secondary schools were interviewed. The chapter discusses the impact of empowerment on the orchestration and design of assessment activities and responsive practices in determining students’ performance. The chapter also highlights the challenges faced by PE teachers in implementing SBA and in assessing students’ ability and how they overcame these challenges. The empowerment had inspired the PE teachers to reconsider their role and the status of PE education in secondary schools. PE teachers began to accept the fact that they are now becoming significant in SBA, and they need to function effectively as assessors within SBA.